√(X+10) + √(X-6) = 8
Help would be greatly appreciated! Thanks!
2 answers
x=+-√(14
sqrt(x-6)+sqrt(x+10) = 8
sqrt(x-6) = 8 - sqrt(x+10)
Square both sides
x - 6 = (8 - sqrt(x + 10))^2
Expand out terms on the right hand side
x - 6 = x - 16sqrt(x + 10) + 74
16sqrt(x + 10) = 80
Divide both sides by 16
sqrt(x + 10) = 5
Square both sides
x + 10 = 25
x = 15
sqrt(x-6) = 8 - sqrt(x+10)
Square both sides
x - 6 = (8 - sqrt(x + 10))^2
Expand out terms on the right hand side
x - 6 = x - 16sqrt(x + 10) + 74
16sqrt(x + 10) = 80
Divide both sides by 16
sqrt(x + 10) = 5
Square both sides
x + 10 = 25
x = 15